(untitled) (Journal of Parents and Teachers, 2014)
Teaching card of the film Havana Blues directed by Benito Zambrano about different topics. In this film we can see values, music, economic systems like communism and capitalism. From activities to do before watching the film, while watching it and after the visualization, there are activities to work with humiliation, passion, freedom, sacrifice, cruelty, love, lie, withdrawal and suffering.